Mental contrasting with implementation intentions increases study time for university students. (14th December 2020) - Clark, Melinda; Miller, Anthony; Berry, Jamie; Cheng, Ken
Abstract : Background: Goal setting is a core aspect of human behaviour that drives action. The intention to achieve one's goals, however, does not necessarily translate into desired outcomes. Although the mental contrasting with implementation intentions (MCII) strategy has demonstrated strong efficacy, limited investigations have been conducted in a university academic goal‐setting context. Aims: The current study sought to investigate the efficacy of MCII in facilitating academic goal attainment in university students. Method: Fifty‐eight students from Macquarie University, Australia, were randomly allocated to either MCII or stress management training, and were assessed on their progress towards the target goal of increased hours of study four weeks later. Goal attainment scaling (GAS) facilitated the generation of tailored specific goals and was the primary outcome measure. Results: An analysis of covariance indicated that students trained in MCII achieved significantly better goal outcomes than those trained in stress management for both broad ( p  = .038) and course‐ or unit‐specific ( p  = .005) study goals. Conclusions: Results highlight the efficacy of using MCII and GAS in combination to promote increased study time for university students.